Determinants of Success in Graduation: An Empirical Study - Marius GIUCLEA; Alexandru AGAPIE; Luiza BĂDIN; Silvia DEDU; Ileana MIRCIOI (VĂLIMĂRANU); Ovidiu SOLOMON; Rareș BITEȘ (Revista de Management Comparat International, 2021)
One of the most concerning problems that higher education institutions are facing recently is the high dropout rate of students enrolled at all levels of study. Consequently, the dropout phenomenon and the determinants of success in completing university studies are increasingly attracting the attention of both researchers and decision makers. This paper revisits the problem of identifying the factors accountable for success in higher education and complements the aspects addressed in Agapie et al. (2020) by suggesting a basic set of measures based on Agglomerative Hierarchical Clustering (AHC).